Polymer, electrolyte material, electrolyte membrane, electrolyte membrane with catalyst layer, membrane electrode assembly, solid polymer fuel cell, and solid polymer water electrolysis device
By designing polymers with specific structures and combining them with ion exchange groups and cross-linking structures, the problem of insufficient proton conductivity of non-fluorinated polymers was solved, and an electrolyte material with high proton conductivity and gas barrier properties was achieved, which is suitable for fuel cells and water electrolysis devices.
Patent Information
- Application Number
- CN202480013385.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-01-29
- Filing Date
- 2024-03-26
- Publication Date
- 2025-09-16
AI Technical Summary
In the existing technology, the proton conductivity of non-fluorinated polymers is insufficient and cannot meet the requirements of efficient energy conversion.
A polymer with a specific structure, a structural unit A1 containing an ion exchange group and a structural unit A2 without an ion exchange group are connected by a cross-linking group to form a microphase separation structure, thereby improving proton conductivity.
It achieves high proton conductivity and excellent gas barrier properties, making it suitable as an electrolyte material for use in high-humidity environments, improving the performance of fuel cells and water electrolysis devices.
Smart Images

Figure CN120659827A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a polymer, an electrolyte material, an electrolyte membrane, an electrolyte membrane with a catalyst layer, a membrane electrode assembly, a solid polymer fuel cell, and a solid polymer water electrolysis device. Background Art
[0002] In recent years, fuel cells have attracted attention as a highly energy-efficient new energy technology, driven by environmental concerns. Among these technologies, solid polymer fuel cells, which use polymer (macromolecule) materials as electrolytes, have a high maximum current density and operate at low temperatures, making them particularly attractive as power sources for mobile devices such as automobiles and small-capacity power sources for portable electronic devices. Furthermore, from the perspective of carbon neutrality, the utilization of solid polymer fuel cell hydrogen energy, which utilizes fuel cell technology, is also attracting attention.
[0003] Fluoropolymers are known as polymers used in electrolytes for polymer electrolyte fuel cells and water electrolysis (electrolyte polymers) (see, for example, Patent Document 1). Fluoropolymers are widely used in electrolyte applications due to their high proton conductivity, but they are associated with high costs and significant environmental impact.
[0004] For these reasons, the development of fluorine-free electrolyte polymers is underway. For example, Patent Document 2 discloses an invention relating to a polymer electrolyte membrane comprising a block copolymer each containing one or more segments (A1) containing an ionic group and one or more segments (A2) containing no ionic group.
[0005] Prior art literature Patent Literature Patent Document 1: Japanese Patent Application Laid-Open No. 11-204119 Patent Document 2: International Publication No. 2013-031675 Summary of the Invention
[0006] Technical problem to be solved by the invention However, the non-fluorinated polymer obtained by block copolymerization disclosed in Patent Document 2 does not necessarily have sufficient proton conductivity.
[0007] One aspect of the present disclosure aims to provide a polymer having excellent proton conductivity as an electrolyte.
[0008] Technical solutions to technical problems The present disclosure provides the following [1] to
[16] in several aspects. [1] A polymer having a structure represented by the following formula (1).
[0010] [Chemistry 1]
[0011] [In formula (1), A 1 represents a structural unit represented by the following formula (a1), A 2 represents a structural unit represented by the following formula (a2), L 1 and L 2 Each independently represents a single bond, -O-, -S- or -SO2-, n represents an integer from 10 to 100, Indicates a bond.
[0012] Multiple A 1 Same as each other, Multiple A 2 Same as each other, Multiple L 1 They can be the same or different from each other. Multiple L 2 They may be the same or different from each other.] [Chemistry 2]
[0013] [In formula (a1), IExG represents an ion exchange group, L 3 represents a single bond, -O-, -S-, -SO2- or -CO-, x represents an integer from 2 to 10, Indicates a bond.
[0014] Multiple IExGs can be the same or different from each other. Multiple L 3 They may be the same or different from each other.] [Chemistry 3]
[0015] [In formula (a2), Ar represents an arylene group having no ion exchange group, L 4 represents a single bond, -O-, -S-, -SO2- or -CO-, y represents an integer from 3 to 20, Indicates a bond.
[0016] Multiple Ar may be the same or different from each other. Multiple L 4 They may be the same or different from each other.] [2] The polymer according to [1], wherein the L 1 、the L 2 、the L 3 and the L 4 Each is independently a single bond or -SO2-. [3] The polymer according to [1] or [2], wherein the structural unit represented by the formula (a1) contains at least one selected from a sulfo group, an alkylsulfo group, and a sulfonimide group as the ion exchange group. [4] The polymer according to any one of [1] to [3], wherein the structural unit represented by the formula (a2) contains at least one selected from a phenylene group, a naphthylene group, and a fluorenyl group as the arylene group. [5] The polymer according to any one of [1] to [4], wherein the polymer has a number average molecular weight of 20,000 to 300,000. [6] The polymer according to any one of [1] to [5], wherein the polymer is a polymer of a compound represented by the following formula (b1) and a compound represented by the following formula (b2), or an oxide thereof.
[0021] [Chemistry 4]
[0022] [In formula (b1), A 1 Same as above, X 1b and X 2b Each independently represents a halogen atom.] [Chemistry 5]
[0023] [In formula (b2), A 2 Same as above, Z 1b and Z 2b Each independently represents a hydroxyl group, a thiol group, a halogen atom, a boronic acid group, an alkyl borane group, or a borate ester group.] [7] The polymer according to any one of [1] to [6], wherein the polymer comprises a plurality of polymer units having a structure represented by the above formula (1), and There are three or more cross-linking groups bonded to the polymer units. [8] The polymer according to [7], wherein the crosslinking group has one or more aromatic rings, The polymer unit is bonded to the aromatic ring. [9] The polymer according to [7] or [8], wherein the polymer is a reaction product of a compound represented by the following formula (b1) and a polymer of a compound represented by the following formula (b2) or an oxide thereof, and a compound having three or more groups that react with the polymer or the oxide thereof to form a crosslink.
[0026] [Chemistry 6]
[0027] [In formula (b1), A 1 Same as above, X 1b and X 2b Each independently represents a halogen atom.] [Chemistry 7]
[0028] [In formula (b2), A 2 Same as above, Z 1b and Z 2b Each independently represents a hydroxyl group, a thiol group, a halogen atom, a boronic acid group, an alkyl borane group, or a borate ester group.]
[10] The polymer according to any one of [1] to [9], wherein the ratio of the weight average molecular weight to the number average molecular weight is 2.0 to 20.0.
[11] An electrolyte material comprising the polymer described in any one of [1] to
[10] .
[12] An electrolyte membrane comprising the polymer described in any one of [1] to
[10] .
[13] An electrolyte membrane with a catalyst layer comprises the electrolyte membrane described in
[12] and a catalyst layer arranged on one surface or both surfaces of the electrolyte membrane.
[14] A membrane electrode assembly comprising the electrolyte membrane described in
[12] and electrode layers arranged on one or both surfaces of the electrolyte membrane.
[15] A solid polymer fuel cell comprising the membrane electrode assembly described in
[14] .
[16] A solid polymer water electrolysis device comprising the membrane electrode assembly described in
[14] .
[0035] Effects of the Invention According to one aspect of the present disclosure, a polymer having excellent proton conductivity as an electrolyte can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a graph showing the SAXS scattering intensity of the electrolyte membrane of Example 1. DETAILED DESCRIPTION
[0037] The following describes exemplary embodiments of the present disclosure. However, the present disclosure is not limited to the following embodiments. It should be noted that, in this specification, the numerical range represented by "to" represents a range that includes the numerical values recorded before and after the "to" as the minimum and maximum values, respectively. In addition, except for specific descriptions, the units of the numerical values recorded before and after the "to" are the same. In addition, the upper and lower limits recorded separately can be combined arbitrarily.
[0038] <Polymer> The polymer according to one embodiment (hereinafter also referred to as “polymer (P)”) has a structure represented by the following formula (1).
[0039] [Chemistry 8]
[0040] In formula (1), A 1 represents a structural unit represented by the following formula (a1) (hereinafter also referred to as "structural unit A 1 ”), A 2 represents a structural unit represented by the following formula (a2) (hereinafter also referred to as "structural unit A 2 ”), L 1 and L 2 Each independently represents a single bond, -O-, -S- or -SO2-, n represents an integer from 10 to 100, Indicates a bond. Multiple A 1 Same as each other, multiple A 2 Same as each other, multiple L 1 They can be the same or different. 2 They can be the same or different from each other.
[0041] [Chemistry 9]
[0042] In formula (a1), IExG represents an ion exchange group, L 3 represents a single bond, -O-, -S-, -SO2- or -CO-, and x represents an integer from 2 to 10, Indicates a bond. Multiple IExGs can be the same or different. 3 They can be the same or different from each other.
[0043] [Chemistry 10]
[0044] In formula (a2), Ar represents an arylene group having no ion exchange group, and L 4 represents a single bond, -O-, -S-, -SO2- or -CO-, y represents an integer from 3 to 20, Represents a bond. Multiple Ar can be the same or different. 4 They can be the same or different from each other.
[0045] Polymer (P) is a so-called electrolyte polymer and has excellent proton conductivity. Therefore, a membrane (polymer electrolyte membrane) formed from polymer (P) exhibits excellent proton conductivity. The reason why polymer (P) has excellent proton conductivity is not clear, but it is speculated that it is due to the presence of multiple identical hydrophilic structural units A. 1 (hydrophilic part) and multiple hydrophobic structural units A identical to each other 2 (hydrophobic part) is precisely arranged, so the ion exchange groups are arranged at equal intervals, and the ion exchange groups self-stack in a high-order structure to induce a microphase separation structure, which is presumed to form a good proton conduction path in the polymer (P). In addition, it is presumed that the structural unit A 1 The dense presence of three or more ion exchange groups in the matrix also contributes to improved phase separation and proton conductivity. These effects are particularly pronounced in high humidity environments (e.g., humidity of 80% RH or higher).
[0046] Polymer (P) tends to exhibit excellent gas barrier properties even when formed into films. The reason for this is presumably as follows. It is believed that because the main chain of polymer (P) is composed of an arylene group containing a benzene ring, the solubility of hydrogen and oxygen is low, and segment motion is restricted, suppressing gas diffusion within the film. This results in excellent gas barrier properties when formed into a film.
[0047] (Polymer (P)) As shown in formula (1), the polymer (P) has a structural unit A 1 With structural unit A 2 Via the linker (L 1 or L 2) and a continuous repeating structure (the structure within [] in formula (1)). The number of repetitions (n) of this structure is 10 to 100, and may be 15 or more, 20 or more, 80 or less, or 50 or less. When the number of repetitions (n) is 15 or more, there is a tendency for excellent gas barrier properties, while when the number of repetitions (n) is 50 or less, there is a tendency for excellent solubility in solvents and film-forming properties. The number of repetitions (n) of this structure is preferably 15 to 80, and more preferably 20 to 50.
[0048] [Structural unit A 1 ] Structural unit A 1 An aromatic ring having an ion exchange group (IExG) is connected via a linker group (L 3 ) and continuous structure.
[0049] Ion exchange groups, also known as ionic groups, have the property of releasing ions (such as cations) and exchanging ions with other ions. Examples of ion exchange groups include sulfo groups, alkylsulfo groups, perfluoroalkylsulfo groups, sulfonimide groups, phosphonic acid groups, phosphoric acid groups, and carboxyl groups. It should be noted that these ion exchange groups also include ion exchange groups that form salts. For example, a "sulfo group" is represented by -SO3M 1 / q (M represents H or a metal (e.g., Li, Na, K, Rb, Cs, Mg, Ca, Sr, Ba, Ti, Al, Fe, Pt, Rh, Ru, Ir, Pd), q represents the valence of M (e.g., an integer from 1 to 4)). The metal represented by M exists in the form of an ion (cation) and reacts with -SO3 - Forming salts.
[0050] Alkylsulfonyl, for example, represented by -R 1 SO3M 1 / q Indicates. R 1 is an alkylene group, and the number of carbon atoms thereof is preferably 1 to 12. 1 Specific examples of include methylene, 1,4-butylene, and 1,6-hexylene. M and q have the same meanings as above.
[0051] Sulfonimide groups, for example, -SO2NM 1 / q SO2R 2 Indicates. R 2 is an alkyl group, and the number of carbon atoms thereof is preferably 1 to 6. 2 Specific examples of include methyl, ethyl and propyl. M and q have the same meanings as above.
[0052] From the viewpoint of obtaining more excellent proton conductivity, the structural unit A as an ion exchange group 1It preferably contains at least one group selected from a sulfo group, an alkylsulfo group, and a sulfonimide group, and more preferably contains a sulfo group. From the same viewpoint, it is further preferred that the structural unit A 1 Most of the ion exchange groups present in the above preferred embodiment are groups, and structural unit A is particularly preferred. 1 All of the multiple ion exchange groups present in are the groups in the above-mentioned preferred embodiment.
[0053] From the viewpoint of obtaining more excellent proton conductivity, the linking group (L 3 ), structural unit A 1 It preferably contains at least one group selected from -SO2- and -CO-, and more preferably contains -SO2-. From the same viewpoint, it is further preferred that the structural unit A 1 The presence of multiple linking groups (L 3 ) are groups in the above-mentioned preferred form.
[0054] From the viewpoint of achieving both superior proton conductivity and chemical durability, the structural unit A 1 The linking group (L 3 ) is preferably a single bond or -SO2-.
[0055] Linking group (L 3 ) is not particularly limited, but is preferably located at the ortho or meta position relative to the ion exchange group, more preferably at the ortho position. 1 It preferably contains a 1,4-phenylene group having an ion exchange group.
[0056] From the viewpoint of obtaining more excellent proton conductivity and excellent hot water resistance, the structural unit A 1 The number of repetitions (x) of the structure in [ ] in formula (a1) is preferably 2-8, more preferably 3-5.
[0057] From the viewpoint of obtaining more excellent proton conductivity, the structural unit A 1 It preferably contains at least one structure selected from the group consisting of a structure represented by the following formula (a1-1) (hereinafter referred to as “structure (a1-1)”) and a structure represented by the following formula (a1-2) (hereinafter referred to as “structure (a1-2)”).
[0058] [Chemistry 11]
[0059] [Chemistry 12]
[0060] IExG and The same as above. Multiple IExGs may be the same or different. 1 represents an integer from 2 to 10, and x in formula (a1-2) 2 represents an integer from 2 to 5. 1 When both structure (a1-1) and structure (a1-2) are included, x 1 with 2x 2 The total is 2 to 10. 1 It is preferably 2 to 5, more preferably 2 to 3. 2 It is preferably 2 to 3, and more preferably 2.
[0061] Structural unit A 1 It may contain only structure (a1-1) or it may contain structure (a1-1) and structures other than structure (a1-1). In the latter case, structure (a1-1) and structures other than structure (a1-1) may be connected by a linking group (L 3 ) are linked. Similarly, structural unit A 1 It may contain only structure (a1-2) or it may contain structure (a1-2) and structures other than structure (a1-2). In the latter case, structure (a1-2) and structures other than structure (a1-2) may be linked by a linking group (L 3 )link.
[0062] As structural unit A 1 Specific examples include structural units represented by the following formulae (A1-1) to (A1-4).
[0063] [Chemistry 13]
[0064] IExG and , and L in formula (A1-3) to formula (A1-4) 3 Same as above. Multiple IExG can be the same or different. 3 They can be the same or different from each other.
[0065] From the viewpoint of obtaining more excellent proton conductivity and excellent chemical durability, the structural unit A in the polymer (P) 1 Any one of the structural units represented by formula (A1-1) to formula (A1-4) is preferred, and the structural unit represented by formula (A1-2) is more preferred.
[0066] [Structural unit A 2 ] Structural unit A 2The arylene group (Ar) without an ion exchange group is connected to the arylene group (L) via a linking group (L 4 ) and continuous structure.
[0067] An arylene group is a divalent aromatic hydrocarbon group having a structure obtained by removing two hydrogen atoms from an aromatic hydrocarbon. From the perspectives of solubility in solvents and film-forming properties, the number of aromatic rings possessed by the arylene group is preferably 1 to 4, more preferably 1 to 2, and even more preferably 1. The arylene group may have a substituent other than an ion-exchange group, but preferably has no substituent.
[0068] Specific examples of the arylene group include a phenylene group, a naphthylene group, a fluorenylene group, an anthrylene group, a phenanthrenylene group, a triphenylene group, a pyrenylene group, and a naphthylene group.
[0069] From the viewpoint of solubility in solvents and film forming properties, the structural unit A is 2 It preferably contains at least one selected from phenylene, naphthylene and fluorenyl, more preferably contains phenylene, and even more preferably contains 1,4-phenylene. From the same viewpoint, it is further preferred that the structural unit A 2 The majority of the arylene groups present in the above preferred embodiment are groups, and the structural unit A is particularly preferred. 2 The multiple arylene groups present in are all independently phenylene, naphthylene or fluorenyl.
[0070] From the viewpoint of excellent solubility in solvents and film-forming properties, and excellent mechanical strength during film formation, as the linking group (L 4 ), structural unit A 2 It preferably contains at least one group selected from -SO2-, -CO- and a single bond, and more preferably contains -SO2- or -CO-. From the same viewpoint, it is further preferred that the structural unit A 2 The presence of multiple linking groups (L 4 ) are the groups of the preferred embodiment described above, the structural unit A 2 The presence of multiple linking groups (L 4 ) can all be groups in the preferred forms described above.
[0071] From the viewpoint of excellent chemical durability, structural unit A 2 The linking group (L 4 ) is preferably a single bond or -SO2-.
[0072] From the viewpoint of obtaining more excellent proton conductivity and excellent hot water resistance, the structural unit A 2 The number of repetitions (y) of the structure in [ ] in formula (a2) is preferably 4-12, more preferably 5-10.
[0073] From the viewpoint of achieving both superior proton conductivity and hot water resistance, the structural unit A 2 The number of repetitions (y) of the structure in [ ] in formula (a2) is preferably 2 to 7 more than the number of repetitions (x) of the structure in [ ] in formula (a1) (x + (2 to 7)).
[0074] From the viewpoint of excellent solubility in solvents and film-forming properties, and excellent mechanical strength during film formation, the structural unit A 2 It is preferable that the structure includes at least one selected from the group consisting of the structure represented by the following formula (a2-1) and the structure represented by the following formula (a2-2).
[0075] [Chemistry 14]
[0076] [Chemistry 15]
[0077] Ar and The same as the above meaning. A plurality of Ar may be the same as or different from each other.
[0078] As structural unit A 2 Specific examples include the structural unit represented by the following formula (A2).
[0079] [Chemistry 16]
[0080] Ar and L in formula (A2) 4 and As defined above, Q represents a group having a structure represented by formula (a2-1) or formula (a2-2), and y 1 and y 2 Each independently represents an integer of 2 to 4. 1 and y 2 The number of Ar may be the same as or different from each other, and the number of L may be 2 to 3. 4 They can be the same or different from each other.
[0081] [Linking group] From the viewpoint of obtaining more excellent proton conductivity and excellent chemical durability, as the structural unit A 1 With structural unit A 2 The connecting group between 1 or L 2 ), the polymer (P) preferably contains at least one group selected from a single bond, -SO2- and -S-, and more preferably contains -SO2-. From the same viewpoint, it is further preferred that the multiple structural units A present in the polymer (P)1 With structural unit A 2 The connecting group between 1 and L 2 ) are preferably groups of the above preferred embodiment, and it is particularly preferred that multiple structural units A exist in the polymer (P) 1 With structural unit A 2 The connecting group between 1 and L 2 ) are all groups in the above-mentioned preferred embodiments.
[0082] From the viewpoint of obtaining more excellent proton conductivity and excellent chemical durability, the structural unit A in the polymer (P) 1 With structural unit A 2 The connecting group between 1 and L 2 ) are preferably each independently a single bond or -SO2-.
[0083] As mentioned above, the polymer (P) has, in addition to the structural unit A 1 With structural unit A 2 The connecting group between 1 and L 2 ), in structural unit A 1 Neutralizing structural unit A 2 There is also a linking group (L 3 and L 4 ), from the viewpoint of obtaining more excellent proton conductivity and excellent chemical durability, these linking groups (L 1 , L 2 , L 3 and L 4 ) are particularly preferably each independently a single bond or -SO2-.
[0084] The polymer (P) may be composed of a structure represented by formula (1) and a terminal structure bonded to the structure. The polymer (P) may be, for example, a compound represented by the following formulas (1-1) to (1-3).
[0085] [Chemistry 17]
[0086] A in formulas (1-1) to (1-3) 1 、A 2 , L 1 , L 2 and n have the same meanings as above. 2 L 2 is a single bond. 1 and Z 2Each independently represents a hydroxyl group, a thiol group, a halogen atom, a boronic acid group, an alkylboryl group, or a borate ester group. Examples of halogen atoms include fluorine (F), chlorine (Cl), bromine (Br), and iodine (I). Examples of alkylboryl groups include diethylboryl, bis(3-methyl-2-butyl)borane, dicyclohexylboryl, and 9-borabicyclo[3.3.1]nonyl. Examples of borate ester groups include pinacol borate, 1,3-propylene glycol borate, bicyclohexyl glycol borate, neopentyl glycol borate, and catechol borate.
[0087] The polymer (P) may include a plurality of polymer units having the structure represented by formula (1) (hereinafter also referred to as "polymer units A"). For example, the polymer (P) may include three or more polymer units A and three or more crosslinking groups bonded to the polymer units A. A polymer (P) having such crosslinking groups (hereinafter also referred to as "crosslinked polymer (P')") exhibits excellent swelling resistance.
[0088] The polymer unit A, for example, has the terminal group Z removed from any of the compounds represented by the above formulae (1-1) to (1-3). 1 and Z 2 Of the two terminal groups of polymer unit A, the terminal group bonded to the crosslinking group can be A 1 , or A 2 The terminal group bonded to the cross-linking group is L 2 In the case of a single bond as shown (ie, in formula (1-1) and formula (1-2) with Z 2 Bonded to L 2 In the case of ), the terminal group bonded to the cross-linking group is regarded as A 2 The two terminal groups of polymer unit A may be bonded to different crosslinking groups. Of the two terminal groups of polymer unit A, the terminal group on the opposite side to the terminal group bonded to the crosslinking group may be bonded to the terminal group Z 1 and Z 2 The plurality of polymer units A bonded to one crosslinking group may be the same as or different from each other.
[0089] The cross-linking group may be a group derived from a known cross-linking compound. From the perspective of chemical stability, the cross-linking group preferably has one or more aromatic rings. In this case, it is preferred that the polymer unit A is bonded to the aromatic ring of the cross-linking group. The polymer unit A may be directly bonded to the aromatic ring or bonded to the aromatic ring via -O-, -S-, or -SO2-. The number of aromatic rings present in the cross-linking group is preferably 1 or 2.
[0090] The cross-linking group may be, for example, a group represented by the following formula (c).
[0091] [Chemistry 18]
[0092] In formula (c), E represents a hydroxyl group, a thiol group, a halogen atom, a boronic acid group, an alkyl borane group or a borate ester group, and L 5 Represents a single bond, -O-, -S-, -SO2- or -CO-, L 6 represents a single bond, -O-, -S- or -SO2-, represents a bond to the polymer unit A, p, q, r and s each represent an integer of 0 to 5, and z represents 0 or 1. In the case where p+q is 3 or more, p+r is 0 to 5, q+s is 0 to 5, and z is 0, r and p are 0. When there are multiple E's, the multiple E's may be the same or different. When there are multiple L's 5 In the case of multiple L 5 They can be the same or different. 6 They can be the same or different from each other.
[0093] The group represented by formula (c) may be, for example, a group represented by the following formulas (c1) to (c5). The symbols in formulas (c1) to (c5) have the same meanings as described above. Some or all of the E groups in the groups represented by formulas (c1) to (c5) may be replaced by hydrogen atoms.
[0094] [Chemistry 19]
[0095] The number of crosslinking groups contained in the crosslinked polymer (P') may be 1 or plural, and the plural crosslinking groups may be the same as or different from each other.
[0096] The crosslinked polymer (P') may include a crosslinking group bonded to two polymer units A. Such a crosslinking group may have the same structure as the above-mentioned crosslinking group bonded to three or more polymer units A, except that the number of bonds bonded to polymer units A is different.
[0097] From the perspective of achieving superior proton conductivity, the proportion of the structure represented by formula (1) in the entire polymer (P) is preferably 80% by mass or greater. From the same perspective, the proportion of the structure represented by formula (1) in the entire polymer (P) may be 85% by mass or greater, or 90% by mass or greater. The proportion of the structure represented by formula (1) in the entire polymer (P) may be less than 100% by mass. The proportion of the structure represented by formula (1) in the entire polymer (P) may be 80% by mass or greater and less than 100% by mass, or 85% by mass or greater and less than 100% by mass.
[0098] The polymer (P) may contain fluorine atoms. The fluorine content in the polymer (P) is preferably 5% by mass or less. The polymer (P) preferably contains no fluorine atoms (the fluorine content is below the detection limit).
[0099] From the perspective of achieving superior proton conductivity and excellent mechanical strength during membrane formation, the number average molecular weight of the polymer (P) may be 20,000 or greater, 25,000 or greater, or 30,000 or greater. From the perspective of excellent solubility in solvents and excellent membrane forming properties, the number average molecular weight may be 300,000 or less, 200,000 or less, or 150,000 or less. From these perspectives, the number average molecular weight of the polymer (P) may be 20,000 to 300,000, 25,000 to 200,000, or 30,000 to 150,000.
[0100] From the perspective of achieving superior proton conductivity and excellent mechanical strength during membrane formation, the weight-average molecular weight of the polymer (P) may be 40,000 or greater, 50,000 or greater, or 60,000 or greater. From the perspective of excellent solubility in solvents and excellent membrane-forming properties, the weight-average molecular weight of the polymer (P) may be 500,000 or less, 300,000 or less, or 200,000 or less. From these perspectives, the weight-average molecular weight of the polymer (P) may be 40,000 to 500,000, 50,000 to 300,000, or 60,000 to 200,000.
[0101] The ratio of the weight-average molecular weight to the number-average molecular weight (polydispersity) of the polymer (P) may be 2.0 or greater, 2.5 or greater, or 2.8 or greater. A polydispersity of 2.5 or greater for the polymer (P) tends to yield excellent swelling resistance. From the perspective of solubility in solvents, the polydispersity of the polymer (P) may be 20.0 or less, 15.0 or less, or 10.0 or less. The polydispersity of the polymer (P) may be 2.0 to 20.0, 2.5 to 20.0, 2.5 to 15.0, or 2.8 to 10.0.
[0102] The number average molecular weight and weight average molecular weight of the polymer (P) are values calculated based on standard polyethylene glycol / oxide (PEG / PEO) measured by gel permeation chromatography (GPC).
[0103] The polymer (P) can be obtained, for example, by reacting (polymerizing) a compound represented by the following formula (b1) (hereinafter also referred to as "compound (b1)") with a compound represented by the following formula (b2) (hereinafter also referred to as "compound (b2)." In other words, the polymer (P) can be a polymer of the compound (b1) and the compound (b2).
[0104] [Chemistry 20]
[0105] In formula (b1), A 1 Same as above, X 1b and X 2b Each independently represents a halogen atom. Examples of the halogen atom include a fluorine atom (F), a chlorine atom (Cl), a bromine atom (Br), and an iodine atom (I).
[0106] [Chemistry 21]
[0107] In formula (b2), A 2 Same as above, Z 1b and Z 2b Each independently represents a hydroxyl group, a thiol group, a halogen atom, a boronic acid group, an alkyl borane group or a borate group. Examples of halogen atoms, alkyl borane groups and borate groups are the same as those of Z above. 1 and Z 2 The same are shown as examples of the halogen atom, alkylboryl group and borate group.
[0108] In the above method, the structural unit A can be formed throughout the entire polymer. 1 With structural unit A 2 Therefore, according to the above method, the number of repetitions n in formula (1) can be easily set to 10 or more.
[0109] According to the above method, L in formula (1) can be obtained 1 and L 2 The polymer (P) is -O-, -S- or a single bond. Specifically, 1b and Z 2b When at least one of the groups is a hydroxyl group, L in formula (1) can be obtained. 1 and L 2 A polymer (P) wherein at least one of the Z 1b and Z 2bWhen at least one of the groups is a thiol group, L in formula (1) can be obtained. 1 and L 2 A polymer (P) wherein at least one of the Z 1b and Z 2b When at least one of the groups is a halogen atom, a boronic acid group, an alkyl borane group or a boronic acid ester group, L in formula (1) can be obtained. 1 and L 2 A polymer (P) in which at least one of the bonds is a single bond.
[0110] As compound (b1), X can be used. 1b and / or X 2b Similarly, as compound (b2), Z 1b and / or Z 2b Different compounds.
[0111] The compound (b1) and the compound (b2) can be reacted (polymerized) by, for example, an aromatic nucleophilic substitution reaction in a solvent in the presence of a base.
[0112] The solvent used in the reaction is preferably a good solvent for Compound (b1), Compound (b2), and the polymer (P), and preferably one that can increase the molecular weight of the polymer (P) during polymerization. For example, N-methylpyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, diphenyl sulfone, sulfolane, 1,3-dimethyl-2-imidazolidinone, and tetramethylurea are preferably used. These solvents may be used alone or as a mixture of two or more.
[0113] The base is used to increase the nucleophilicity of compound (b2). The base is not particularly limited as long as it can deprotonate compound (b2). For example, hydroxides and carbonates of alkali metals (lithium, sodium, potassium, rubidium, and cesium), hydroxides and carbonates of alkaline earth metals (magnesium, calcium, strontium, and barium), and organic bases such as amines can be used.
[0114] The reaction temperature may be in the range of 25° C. to 350° C. From the viewpoint of excellent reaction rate, the reaction temperature is preferably 60° C. or higher, more preferably 100° C. or higher. From the viewpoint of suppressing polymer decomposition, the reaction temperature is preferably 300° C. or lower, more preferably 250° C. or lower.
[0115] Compound (b1) and Compound (b2) can also react (polymerize) by a cross-coupling reaction in a solvent in the presence of a catalyst. Examples of solvents that can be used in the reaction are the same as those that can be used in the aromatic nucleophilic substitution reaction described above.
[0116] As a catalyst, there is no particular limitation as long as it can carry out the cross-coupling reaction, and conventionally known catalysts can be used. If it is a coupling reaction between halogens, for example, a copper catalyst, a nickel catalyst, or a palladium catalyst can be used. If it is a coupling reaction between a halogen and a boronic acid group, an alkyl borane group, or a borate ester group, for example, conventionally known catalysts (palladium catalysts, nickel catalysts, etc.) used in the Suzuki-Miyaura coupling reaction can be used.
[0117] Examples of the copper catalyst include copper(I)-2-thiophenecarboxylate and copper(I) tetraacetonitrile hexafluorophosphate.
[0118] Examples of the nickel catalyst include bis(1,5-cyclooctadiene)nickel(0), dibromobis(triphenylphosphine)nickel(II), and [1,1′-bis(diphenylphosphino)ferrocene]dichloride nickel(II).
[0119] Examples of the palladium catalyst include tetrakis(triphenylphosphine)palladium(0), palladium(II) acetate, bis(triphenylphosphine)palladium(II) dichloride, and [1,1′-bis(diphenylphosphino)ferrocene]palladium(II) dichloride.
[0120] The reaction temperature may be in the range of 0° C. to 350° C. From the viewpoint of excellent reaction rate, the reaction temperature is preferably 30° C. or higher, more preferably 60° C. or higher. From the viewpoint of suppressing polymer decomposition, the reaction temperature is preferably 300° C. or lower, more preferably 250° C. or lower.
[0121] In the aromatic nucleophilic substitution reaction and cross-coupling reaction described above, water is preferably removed from the reaction system to increase the molecular weight of the polymer (P). The dehydration method is not particularly limited; examples include methods of azeotropic dehydration in the presence of an azeotropic solvent, methods of heating to a temperature above the boiling point of water and continuously removing water from the reaction system, and methods of using a water absorbent such as a molecular sieve. The azeotropic solvent is not particularly limited as long as it can remove water; examples include benzene, toluene, cyclohexane, and xylene.
[0122] The aromatic nucleophilic substitution reaction and cross-coupling reaction are preferably carried out under an inert atmosphere (e.g., nitrogen or argon). After the polymerization reaction is completed, the polymer is recovered from the reaction solution and purified to obtain the desired polymer. Examples of methods for recovering the polymer from the reaction solution include: adding the reaction solution to a solvent in which the polymer has low solubility to precipitate the polymer and recover it as a solid; removing the solvent from the reaction solution by evaporation to recover the polymer as a solid. Examples of methods for purifying the polymer include washing the polymer in a solvent in which the polymer has low solubility and byproduct inorganic salts and residual monomer-derived compounds have high solubility; and washing using a Soxhlet extractor. Methods for recovering and purifying the polymer are not limited to these methods.
[0123] The polymer (P) can also be obtained by oxidizing a polymer having a structure represented by formula (1) (for example, a polymer of compound (b1) and compound (b2)). More specifically, the polymer (P) can be a polymer having a structure represented by formula (1) containing -S- (sulfide group) as L. 1 , L 2 , L 3 or L 4 From the viewpoint of excellent chemical durability, the sulfide-containing polymer is preferably an oxide of a polymer having a structure represented by formula (1). 1 , L 2 , L 3 and L 4 Each independently represents a single bond, -S- or -SO2-.
[0124] The oxidation method for the sulfide-containing polymer is not particularly limited and can be any known method for oxidizing sulfide groups (-S-) to obtain sulfonyl groups (-SO2-). An example of such a method is immersing the sulfide-containing polymer in a mixed solution containing acetic acid, sulfuric acid, and hydrogen peroxide. The concentration of acetic acid in the mixed solution can be, for example, 50 to 90% by mass. The concentration of sulfuric acid in the mixed solution can be, for example, 5 to 25% by mass. The concentration of hydrogen peroxide in the mixed solution can be, for example, 1 to 15% by mass. The immersion time can be, for example, 1 to 100 hours. In the above method, heating can be performed after immersion. The heating temperature can be, for example, 30 to 120°C, and the heating time can be, for example, 0.1 to 24 hours.
[0125] The polymer (P) obtained by the above method is a polymer having a structure represented by formula (1) containing -SO2- (sulfonyl group) as L 1 , L 2 , L 3 or L4 The polymer may be a polymer in which all sulfide groups in the sulfide-containing polymer are oxidized to sulfonyl groups (complete oxide), or a polymer in which a portion of the sulfide groups in the sulfide-containing polymer are oxidized to sulfonyl groups (partial oxide). The degree of oxidation can be adjusted, for example, by adjusting the impregnation time, heating temperature, and heating time.
[0126] The polymer (P) can be obtained by reacting (polymerizing) the compound (b1), a polymer of the compound (b2) or an oxide thereof, and a compound having three or more groups that react with the polymer or oxide thereof to form a crosslink (hereinafter also referred to as "crosslinking compound (d)"). In other words, the polymer (P) may be a reaction product of the compound (b1), the polymer of the compound (b2) or an oxide thereof, and the crosslinking compound (d).
[0127] The above method can produce a crosslinked product (e.g., the crosslinked polymer (P')) having polymer units of a polymer of compound (b1) and compound (b2), or an oxide thereof. This method allows for the formation of a crosslinked structure while maintaining a precise arrangement, achieving both excellent proton conductivity and excellent swelling resistance.
[0128] The crosslinking compound (d) may be a known crosslinking compound, for example, a low molecular weight compound having a molecular weight of 1000 or less. The group that reacts with the polymer or its oxide to form a crosslink is, for example, a hydroxyl group, a thiol group, a halogen atom, a boronic acid group, an alkyl borane group, or a borate ester group.
[0129] From the perspective of chemical stability, the crosslinkable compound (d) preferably has one or more aromatic rings. In this case, the group that reacts with the polymer or its oxide to form a crosslink is preferably directly bonded to the aromatic ring. The number of aromatic rings in the crosslinkable compound (d) is preferably one or two.
[0130] The crosslinking compound (d) may be, for example, a compound represented by the following formula (d).
[0131] [Chemistry 22]
[0132] In formula (d), E, L 5 and z have the same meanings as above, and t and u each represent an integer from 0 to 5. Wherein, t+u is 3 or more, and when z is 0, t is 0. Multiple E's may be the same or different. Among the multiple E's, 3 or more E's may be connected to the terminal group (X) of the above polymer or its oxide. 1b 、X 2b 、Z 1b or Z 2b ) reaction to form cross-links.
[0133] The polymers of the compound (b1) and the compound (b2), their oxides, and the crosslinking compound (d) may be used alone or in combination of two or more.
[0134] The reaction between the compound (b1) and the polymer of the compound (b2) or its oxide and the crosslinking compound (d) can be carried out in the same manner as the reaction between the compound (b1) and the compound (b2).
[0135] <Electrolyte Material and Electrolyte Membrane> An electrolyte material according to one embodiment is an electrolyte-containing material, and includes the aforementioned polymer (P) as an electrolyte. An electrolyte membrane according to one embodiment is an electrolyte-containing membrane, and includes the aforementioned polymer (P) as an electrolyte. The aforementioned electrolyte material is used to form the aforementioned electrolyte membrane. In other words, the aforementioned electrolyte membrane may contain the aforementioned electrolyte material.
[0136] The electrolyte material and the electrolyte membrane contain a polymer (P), and therefore have excellent proton conductivity.
[0137] The electrolyte material and electrolyte membrane can also have a microphase-separated structure when immersed in water (in a wet state). Specifically, when the electrolyte membrane is immersed in water and subjected to small-angle X-ray scattering (SAXS) measurement, the peak spacing obtained can be 4.0 nm or greater.
[0138] The electrolyte material and electrolyte membrane can also have a microphase-separated structure in a vacuum-dried state (dry state). Specifically, when the electrolyte membrane is vacuum-dried and subjected to small-angle X-ray scattering (SAXS) measurement, the peak spacing obtained can be 2.5 nm or greater.
[0139] The electrolyte material and electrolyte membrane may consist solely of the polymer (P) or may contain the polymer (P) and components other than the polymer (P) (such as additives). In other words, the electrolyte material may be a composition. The polymer (P) content in the electrolyte material and electrolyte membrane may be 90-100% by mass, 94-100% by mass, or 97-100% by mass. These contents are based on the total solids content of the electrolyte material or electrolyte membrane.
[0140] Components other than the polymer (P) that may be included in the electrolyte material and electrolyte membrane include water-retaining inorganic substances and free radical scavengers. Specific examples include water, silicon dioxide, cerium oxide, and manganese oxide. These may be used alone or in combination.
[0141] The thickness of the electrolyte membrane is not particularly limited and can be changed according to the size of the fuel cell, etc. From the viewpoint of improving the mechanical strength of the membrane and reducing the membrane resistance, the thickness of the electrolyte membrane can be, for example, 1 to 200 μm. m m, can also be 1 to 100 m m or 1~50 m m.
[0142] The production method of the electrolyte membrane is not particularly limited and can be produced by a method known as a method for forming an electrolyte polymer into a membrane. Examples of the production method of the electrolyte membrane include solution casting, dispersion casting, melt pressing, and melt extrusion.
[0143] In the solution casting method, for example, a solution containing a polymer (P) is used as an electrolyte material, the solution is cast on a substrate, the solvent is removed, and then the membrane is peeled off from the substrate to obtain an electrolyte membrane.
[0144] The solvent used in the solution casting method is not particularly limited as long as it can dissolve the polymer (P). Examples of solvents that can be used include N-methylpyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, diphenyl sulfone, sulfolane, 1,3-dimethyl-2-imidazolidinone, and tetramethylurea. These can be used alone or in combination.
[0145] In the dispersion casting method, for example, a dispersion containing a polymer (P) is used as an electrolyte material, the dispersion is cast onto a substrate, the dispersion medium is removed, and the membrane is peeled off from the substrate to obtain an electrolyte membrane.
[0146] The dispersion medium used in the dispersion casting method is not particularly limited as long as it can disperse the polymer (P). For example, water, ethers, alcohols, ketones, acetonitrile, nitromethane, toluene, xylene, chlorobenzene, and chloroform can be used. Examples of ethers include tetrahydrofuran and diethyl ether. Examples of alcohols include methanol, ethanol, 1-propanol, isopropanol, and 1-butanol. Examples of ketones include acetone and cyclohexanone. These may be used alone or in combination.
[0147] Electrolyte materials and electrolyte membranes are suitable for use in polymer electrolyte fuel cells and polymer electrolyte water electrolysis devices. They can also be used in redox flow batteries, electrochemical hydrogen pumps, chlor-alkali electrolysis devices, solid acid catalysts, membrane humidity control devices, gas separation membranes, and more.
[0148] The electrolyte membrane can also be used by laminating it with a microporous membrane, nonwoven fabric, mesh, etc. That is, another embodiment of the present disclosure is a laminate comprising an electrolyte membrane and another membrane (microporous membrane, nonwoven fabric, mesh, etc.).
[0149] <Electrolyte Membrane with Catalyst Layer> An electrolyte membrane with a catalyst layer according to one embodiment includes the electrolyte membrane according to the above embodiment and a catalyst layer disposed on one surface or both surfaces of the electrolyte membrane.
[0150] The catalyst layer is, for example, a layer composed of an anode catalyst or a cathode catalyst in a polymer electrolyte fuel cell, a polymer electrolyte water electrolysis device, etc. Hereinafter, the layer composed of the anode catalyst is referred to as the anode catalyst layer, and the layer composed of the cathode catalyst is referred to as the cathode catalyst layer.
[0151] The composition of the catalyst layer is not particularly limited. The catalyst layers (anode catalyst layer, cathode catalyst layer) of polymer electrolyte fuel cells and polymer electrolyte water electrolysis devices can have conventionally known compositions. For example, the catalyst layer can be formed from a conductive composition comprising an anode catalyst or cathode catalyst and a conductive material. The catalyst layer may also contain an ionomer.
[0152] As the anode catalyst in the solid polymer fuel cell, a metal catalyst that can promote the oxidation reaction of fuels such as hydrogen can be used. As the anode catalyst in the solid polymer water electrolysis device, a metal catalyst that can promote the oxygen evolution reaction can be used, for example, platinum, gold, silver, palladium, iridium, rhodium, ruthenium, iron, cobalt, nickel, chromium, tungsten, manganese and vanadium, and alloys of two or more thereof can be used. They can be used alone or in combination of two or more.
[0153] As the cathode catalyst in the solid polymer fuel cell, a metal catalyst that can promote the reduction reaction of oxygen can be used. As the cathode catalyst in the solid polymer water electrolysis device, a metal catalyst that can promote the hydrogen evolution reaction can be used. For example, platinum, gold, silver, palladium, iridium, rhodium, ruthenium, iron, cobalt, nickel, chromium, tungsten, manganese and vanadium and two or more alloys thereof can be used. They can be used alone or in combination of two or more.
[0154] As the conductive material, for example, carbon blacks such as furnace black, Ketjen black, channel black, and acetylene black, activated carbon, and graphite can be used. These can be used alone or in combination of two or more.
[0155] Conventionally known materials can be used as ionomers, for example, ionomers containing perfluorinated electrolytes can be used. Alternatively, the aforementioned polymer (P) can be used as an ionomer. Ionomers with high oxygen permeability are preferably used. The amount of ionomer added to the catalyst layer is not particularly limited; however, it is preferably adjusted within a range that does not significantly hinder oxygen diffusion.
[0156] The catalyst layer may further contain, as additives, a hydrophobizing agent such as carbon fluoride, a fluorine-containing resin, a binder such as a hydrocarbon resin having a sulfonic group, and the like.
[0157] A stack having an anode catalyst layer and a cathode catalyst layer on each side of an electrolyte membrane (e.g., a stack having a layer structure of "anode catalyst layer / electrolyte membrane / cathode catalyst layer") is also called a CCM (Catalyst Coated Membrane) and is suitable for use in solid polymer fuel cells and solid polymer water electrolysis devices.
[0158] In the above-described embodiment, a laminate including other membranes (microporous membrane, nonwoven fabric, mesh, etc.) described above may be used instead of the electrolyte membrane.
[0159] <Membrane Electrode Assembly> A membrane electrode assembly according to one embodiment includes the electrolyte membrane according to the above embodiment and electrode layers arranged on one or both surfaces of the electrolyte membrane.
[0160] The electrode layer is, for example, a catalyst layer (anode catalyst layer or cathode catalyst layer) in the catalyst-layered electrolyte membrane of the above-mentioned embodiment. Hereinafter, the electrode layer including the anode catalyst layer is referred to as the anode layer, and the electrode layer including the cathode catalyst layer is referred to as the cathode layer.
[0161] The composition of the electrode layer is not particularly limited. The electrode layers (anode layer, cathode layer) of polymer electrolyte fuel cells and polymer electrolyte water electrolysis devices can have conventionally known compositions. For example, the electrode layer can be composed of the aforementioned catalyst layer (anode catalyst layer or cathode catalyst layer) and a gas diffusion substrate. If the catalyst layer itself has gas diffusivity, the electrode layer can also be composed solely of the catalyst layer. For example, a porous membrane can be used as the gas diffusion substrate. Materials that not only have gas diffusivity but also possess hydrophobicity and electrical conductivity (for example, carbon nonwoven fabrics, carbon fiber substrates such as carbon paper, and titanium fiber sintered bodies) can also be used as the gas diffusion substrate.
[0162] A laminate having an anode layer and a cathode layer as electrode layers on both sides of an electrolyte membrane (for example, a laminate having a layer structure of "gas diffusion substrate / anode catalyst layer / electrolyte membrane / cathode catalyst layer / gas diffusion substrate") is also called an MEA (Membrane Electrode Assembly) and is suitable for use in solid polymer fuel cells and solid polymer water electrolysis devices.
[0163] In the above-described embodiment, a laminate including other membranes (microporous membrane, nonwoven fabric, mesh, etc.) described above may be used instead of the electrolyte membrane.
[0164] <Solid Polymer Fuel Cell> A polymer electrolyte fuel cell according to one embodiment includes the membrane electrode assembly according to the above-described embodiment.
[0165] The structure of a polymer electrolyte fuel cell is not particularly limited and, other than using the membrane electrode assembly of the above-described embodiment, can be a conventionally known structure. A polymer electrolyte fuel cell can include, for example, two or more membrane electrode assemblies. The two or more membrane electrode assemblies can be stacked (laminated) with separators interposed therebetween. Separators conventionally known as separators for polymer electrolyte fuel cells can be used as separators.
[0166] <Solid polymer water electrolysis device> A solid polymer water electrolysis device according to one embodiment includes the membrane electrode assembly according to the above embodiment.
[0167] The structure of the solid polymer water electrolysis device is not particularly limited and, aside from using the membrane electrode assembly of the above-described embodiment, can be a conventionally known structure. For example, the solid polymer water electrolysis device may further include a power supply outside the membrane electrode assembly. Furthermore, it may include two or more membrane electrode assemblies.
[0168] Example Hereinafter, the present disclosure will be described in more detail using Examples and Comparative Examples, but the present disclosure is not limited to the following Examples.
[0169] <Synthesis example 1> (Synthesis of hydrophilic monomer (M1)) A 10-liter flask equipped with a dropping funnel, reflux condenser, and mechanical stirrer was purged with nitrogen. 101 g of 4,4'-bis[(4-chlorophenyl)sulfonyl]-1,1'-biphenyl and 4 L of dehydrated tetrahydrofuran were added and stirring was initiated. The mixture was cooled to -70°C in a methanol-dry ice bath, and 320 mL of a 2.6 mol / L n-butyllithium-hexane solution was added dropwise. Stirring was continued for 1 hour while cooling in the bath. 40 mL of sulfurous acid gas was introduced into the flask using nitrogen. Stirring was continued while cooling in the bath for 30 minutes. The bath was then removed and the temperature was raised to 0°C. The precipitated solid was separated by suction filtration and washed with 200 mL of tetrahydrofuran. The recovered solid was dissolved in 2 L of pure water, and 260 mL of 35% aqueous hydrogen peroxide was added. The mixture was stirred for 18 hours. The solid was removed by suction filtration, and 600 g of sodium chloride was added to the recovered filtrate. The precipitated white solid was recovered by suction filtration and purified by recrystallization from water / isopropanol. The resulting solid was dried under reduced pressure to obtain a hydrophilic monomer represented by the following formula (M1). The yield was 65%.
[0170] [Chemistry 23]
[0171] <Synthesis example 2> (Synthesis of hydrophobic monomer (M2)) In a 200 mL flask equipped with a stirrer, Dean-Stark tube, reflux condenser, and calcium chloride tube, 4.0 g of 4,4'-bis[(4-chlorophenyl)sulfonyl]-1,1'-biphenyl, 14.8 g of [1,1'-biphenyl]-4,4'-diol, and 13.2 g of potassium carbonate were placed. 50 mL of N,N-dimethylacetamide (DMAc) and 50 mL of toluene were also added. The mixture was heated to 160°C in an oil bath while stirring, and heating and stirring were continued for 4 hours. The toluene was removed from the Dean-Stark tube, and the temperature was raised to 180°C in an oil bath. After heating, heating and stirring were continued for 8 hours. The reaction mixture was allowed to cool to room temperature and then poured into 200 mL of 10% hydrochloric acid. The precipitated white solid was separated by filtration. The filtered solid was washed with 300 mL of ethanol and dried. The dried solid was purified by recrystallization from NMP / ethanol. The obtained solid was dried under reduced pressure to obtain a hydrophobic monomer (M2) represented by the following formula (M2) with a yield of 50%.
[0172] [Chemistry 24]
[0173] <Synthesis Example 3> (Synthesis of hydrophobic monomer (M3)) A 500 mL flask equipped with a stirrer and condenser was purged with nitrogen. To this flask were added 41 g of 4,4'-thiobisbenzenethiol, 14 g of 4,4'-bis[(4-chlorophenyl)sulfonyl]-1,1'-biphenyl, 80 mL of DMAc, and 4 g of potassium carbonate. The mixture was heated to 100°C in an oil bath while stirring, and heating and stirring were continued for 6 hours. The reaction mixture was allowed to cool, and then 100 mL of 1M hydrochloric acid was added. The precipitated solid was recovered by suction filtration. The recovered solid was dissolved in dichloromethane and purified by silica column chromatography using dichloromethane as the developing solvent. The fraction containing the target product was recovered, and the solvent was distilled off using an evaporator. The resulting solid was purified by recrystallization from dichloromethane. The resulting solid was dried under reduced pressure to obtain a hydrophobic monomer (M3) represented by the following formula (M3). The yield was 40%.
[0174] [Chemistry 25]
[0175] <Synthesis Example 4> (Synthesis of hydrophobic monomer (M4)) A 500mL flask equipped with a stirrer and a condenser was purged with nitrogen. 20g of anhydrous aluminum chloride, 10g of isophthaloyl chloride, and 240mL of 1,2-dichlorobenzene were added to the flask. While stirring the reaction solution, 24g of 3-bromo-1,1'-biphenyl was added dropwise. The reaction solution was heated to 40°C and heated and stirred for 3 hours. After the reaction solution was allowed to cool to room temperature, 900mL of ice-cold 3% hydrochloric acid was added to the reaction solution and stirring was continued at room temperature for 18 hours. The precipitated white solid was recovered by suction filtration and washed with ethanol. The obtained solid was dried under reduced pressure and used in the next reaction.
[0176] 0.80 g of the resulting dry solid, 0.71 g of 4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)phenol, 0.11 g of [1,1'-bis(diphenylphosphino)ferrocene]palladium(II) dichloride dichloromethane adduct, and 0.57 g of sodium carbonate were added to a 100 mL flask and the atmosphere was purged with nitrogen. 30 mL of tetrahydrofuran (THF) was added, and the reaction mixture was heated to 50°C while stirring vigorously. Heating and stirring at 50°C were continued for 22 hours. After the reaction mixture was allowed to cool, 100 mL of chloroform and 100 mL of 5% hydrochloric acid were added to separate the layers, and the organic layer was recovered. The solvent was evaporated using an evaporator, and 20 mL of ethyl acetate was added to resuspend the mixture. The suspension was filtered, the filtrate was recovered, and the solvent was evaporated using an evaporator to obtain an orange oil. The resulting oily substance was dissolved in ethyl acetate and purified by silica gel column chromatography using a 1 / 1 (volume ratio) mixture of ethyl acetate and hexane as the developing solvent. The fraction containing the target product was recovered and the solvent was distilled off using an evaporator. The resulting solid was purified by recrystallization from hot toluene. The resulting solid was dried under reduced pressure to obtain a hydrophobic monomer (M4) represented by the following formula (M4). The yield was 60%.
[0177] [Chemistry 26]
[0178] <Synthesis example 5> (Synthesis of Hydrophobic Monomer (M5)) A hydrophobic monomer (M5) represented by the following formula (M5) was obtained by the same method as in Synthesis Example 4, except that 0.96 g of 4'-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)biphenyl-4-ol was used instead of 4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)phenol. The yield was 47%.
[0179] [Chemistry 27]
[0180] <Synthesis example 6> (Synthesis of hydrophobic monomer (M6)) A 500 mL flask equipped with a stirrer and a condenser was purged with nitrogen. 9.5 g of 2,7-dibromo-9,9-diphenylfluorene, 12.1 g of 4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolane-2-yl)phenol, 19 g of potassium carbonate, 2.0 g of tetrakis(triphenylphosphine)palladium (0), and 250 mL of tetrahydrofuran were added to the flask. The reaction solution was heated to 90°C and continued to heat and stir for 3 hours. After the reaction solution was allowed to cool to room temperature, 200 mL of water and 500 mL of ethyl acetate were added for separation, and the organic layer was recovered. The solvent was distilled off using an evaporator, and the crude product was purified by silica column chromatography using a mixed solvent of ethyl acetate / hexane = 1 / 1 (volume ratio) as the developing solvent. The fraction containing the target product was recovered, and the solvent was distilled off using an evaporator. The obtained solid was dried under reduced pressure to obtain a hydrophobic monomer (M6) represented by the following formula (M6). The yield was 53%.
[0181] [Chemistry 28]
[0182] Comparative Example 1 (Synthesis of Polymer (P1)) To a 100 mL three-necked flask equipped with a nitrogen inlet, a stirrer, and a Dean-Stark tube, 1.334 g of the hydrophobic monomer (M2) obtained in Synthesis Example 2, 0.816 g of disodium diphenylsulfone-4,4'-dichloro-3,3'-disulfonate, and 0.551 g of potassium carbonate were added, and the atmosphere was purged with nitrogen. Then, 10 mL of DMAc and 10 mL of toluene were added. After heating to 160°C and reflux dehydration for 4 hours, the toluene was removed from the Dean-Stark tube. Polymerization was carried out by heating to 180°C for 21 hours. After cooling the reaction solution to room temperature, it was purified by reprecipitation from 300 mL of isopropyl alcohol (IPA), and the solid was recovered by filtration. The recovered solid was washed with water and dried under reduced pressure to obtain a polymer (P1) having the structure represented by the following formula (P1). The yield was 90%. Note that n in formula (P1) is calculated from the number average molecular weight described below. The same applies to n in the formulas (P2) to (P8) described later.
[0183] [Chemistry 29]
[0184] [In formula (P1), M represents Na, K or H, and n represents a positive number (approximately 31).] (Molecular weight determination) The number average molecular weight (Mn) and weight average molecular weight (Mw) of the polymer (P1) were measured under the following conditions to determine the polydispersity (Mw / Mn). Mn was 39,000, Mw was 130,000, and Mw / Mn was 3.3.
[0185] [Measurement conditions] The number average molecular weight (Mn) and weight average molecular weight (Mw) were measured by GPC. The polymer (P1) was dissolved at a concentration of 1 mg / mL in an eluent (N,N-dimethylformamide containing 10 mmol / L lithium bromide) to prepare a sample solution. A Tosoh HLC-8320GPC instrument was used. Two Tosoh TSKgel SuperAWM-H columns (6.0 mm inner diameter, 15 cm length) were used. A differential refractometer was used as the detector. Measurements were performed at a flow rate of 0.6 mL / min and a temperature of 40°C. The number average molecular weight (Mn) and weight average molecular weight (Mw) were calculated using standard polyethylene glycol / oxide (PEG / PEO) conversion. Furthermore, the polydispersity (Mw / Mn) was calculated by dividing the weight average molecular weight (Mw) by the number average molecular weight (Mn).
[0186] (Fabrication of Electrolyte Membrane) The obtained polymer (P1) was dissolved in DMAc to obtain a solution containing 10% by mass of the polymer (P1). The obtained solution was cast on a glass substrate and dried at 60°C for 12 hours to obtain a film (film thickness 24 m m). The film thickness was measured at 25 points on the surface using a PG-02 constant pressure thickness gauge manufactured by TECLOCK CORPORATION, and the average value was used. The obtained film was immersed in 1M hydrochloric acid for 24 hours to remove the metal ions (Na + or K + ) is replaced by a proton (H + ), and then immersed in pure water for thorough washing, and dried under reduced pressure, thereby obtaining the polymer electrolyte membrane of Comparative Example 1 (an electrolyte membrane comprising a proton-substituted polymer (P1), with a thickness of 24 m m).
[0187] (evaluate) [Proton conductivity evaluation] The proton conductivity of the obtained polymer electrolyte membrane was measured by the following method.
[0188] The prepared electrolyte membrane was placed in contact with four platinum wires using a Teflon (registered trademark) measurement cell (BT-115, manufactured by Scribner). After maintaining the membrane at a relative humidity of 70% for two hours, the humidity was increased from 20% and, while maintaining the set humidity, DC resistance measurements were performed using the four-terminal method. The in-plane proton conductivity of the membrane was calculated from the obtained resistance value, the membrane thickness, and the distance between the terminals. The proton conductivity of the polymer electrolyte membrane in this comparative example was 60 mS / cm (80°C, 100% relative humidity).
[0189] [Gas permeability test] The gas permeability of the obtained polymer electrolyte membrane was evaluated according to the gas permeability test method based on the isobaric method (JIS K 7126-2).
[0190] Specifically, a polymer electrolyte membrane is first installed in a sealed state between the two chambers of a permeation cell. Hydrogen is supplied as a measurement gas to one side of the polymer electrolyte membrane, and Ar gas is supplied as a carrier gas to the other side. The relative humidity is adjusted by the humidifier temperature of each supply gas and the cell temperature. The measurement gas that has permeated the polymer electrolyte membrane is supplied to a gas chromatograph together with the carrier gas, and the gas permeability is measured based on the detection data and flow rate. The gas permeability (cm) is calculated based on the obtained gas permeability and the film thickness of the polymer electrolyte membrane. 3 mm / (cm 2 ·s·kPa). The hydrogen permeability of the polymer electrolyte membrane of this comparative example was 0.71×10 -7 cm 3 mm / (cm 2 ·s·kPa)(80℃ relative humidity 60%).
[0191] [Small-angle X-ray scattering (SAXS) measurement] Small-angle X-ray scattering (SAXS) measurements of the polymer electrolyte membrane were performed in a dry state (under vacuum) and a wet state (under water immersion) under the following conditions.
[0192] Device name: NanoSTAR manufactured by Bruker Japan Voltage and current: 45kV and 120mA X-ray wavelength: Cu K α ray Camera length: 104.3cm Exposure time: 60 minutes (dry state), 180 minutes (wet state) For the obtained small-angle scattering distribution, the peak position q max Calculate the surface spacing d (= 2π / q max ). No small-angle scattering peak was observed for the polymer electrolyte (P1) in the dry state, but it was d = 4.0 nm in the wet state.
[0193] [Volume swelling ratio measurement] 3 cm squares were punched out from the resulting polymer electrolyte membrane. The punched-out membranes were immersed in 50 mL of pure water at 80°C for 1 hour. The dimensional changes before and after immersion were measured to calculate the membrane volume. The volume swelling ratio was calculated by dividing the volume of the membrane after immersion by the volume of the membrane before immersion. The volume swelling ratio was 55%.
[0194] Comparative Example 2 In Comparative Example 2, commercially available Nafion TM NR211 (film thickness 25 m m) were used as evaluation samples and various evaluations (proton conductivity evaluation, hydrogen permeability test, SAXS measurement, and volume swelling ratio measurement) were performed in the same manner as in Comparative Example 1. The proton conductivity was 130 mS / cm (80°C, relative humidity 100%), the hydrogen permeability was 1.03×10 -7 cm 3 mm / (cm 2 ·s·kPa) (80℃ relative humidity 60%). The surface spacing d in the dry and wet states measured by SAXS is 3.3nm and 5.3nm respectively. The volume swelling ratio is 61%. It should be noted that in the following examples, the above-mentioned Nafion TM The volume swelling ratio of NR211 was used as a reference. When the volume swelling ratio was 61% or less, the electrolyte membrane was evaluated to have excellent swelling resistance.
[0195] <Example 1> (Synthesis of Polymer (P2)) To a 100 mL three-necked flask equipped with a nitrogen inlet tube, a stirrer, and a Dean-Stark tube, 0.983 g of the hydrophobic monomer (M2) obtained in Synthesis Example 2, 1.181 g of the hydrophilic monomer (M1) obtained in Synthesis Example 1, and 0.507 g of potassium carbonate were added, and nitrogen substitution was performed. Then, 10 mL of dimethyl sulfoxide (DMSO) and 10 mL of cyclohexane were added. After heating to 130°C and reflux dehydration for 4 hours, the cyclohexane was removed from the Dean-Stark tube. Polymerization was carried out while heating to 130°C for 150 hours. After cooling the reaction solution to room temperature, it was reprecipitated and purified from 300 mL of isopropyl alcohol (IPA), and the solid was recovered by filtration. The recovered solid was washed with water and dried under reduced pressure to obtain a polymer (P2) having the structure represented by the following formula (P2). The yield was 97%. The Mn of the polymer (P2) measured in the same manner as in Comparative Example 1 was 30,000, the Mw was 61,000, and the Mw / Mn was 2.0.
[0196] [Chemistry 30]
[0197] [In formula (P2), M represents Na, K or H, and n represents a positive number (about 20).] (Fabrication of Electrolyte Membrane) The obtained polymer (P2) was dissolved in DMSO to obtain a solution containing 10% by mass of the polymer (P2). The obtained solution was cast on a glass substrate and dried at 60°C for 12 hours to obtain a film (film thickness 49 m The obtained membrane was immersed in 1M hydrochloric acid for 24 hours to remove the metal ions (Na + or K + ) is replaced by a proton (H + ), and then immersed in pure water for thorough washing, and dried under reduced pressure, thereby obtaining the polymer electrolyte membrane of Example 1 (an electrolyte membrane comprising a proton-substituted polymer (P2), with a membrane thickness of 49 m m).
[0198] (evaluate) The polymer electrolyte membrane of this example was evaluated using the same methods as in Comparative Example 1 (proton conductivity evaluation, hydrogen permeability test, SAXS measurement, and volume swelling ratio measurement). The proton conductivity was 231 mS / cm (80°C, 100% relative humidity), confirming that the polymer electrolyte membrane of this example has good proton conductivity. The hydrogen permeability was 0.15×10 -7 cm 3 mm / (cm 2 ·s·kPa) (80°C relative humidity 60%), it was confirmed that the polymer electrolyte membrane of this embodiment has a higher TM NR211 has better gas barrier properties. In SAXS measurement, Figure 1 As shown, clear peaks were observed in both the dry and wet states. The interplanar spacing d measured by SAXS was 3.6 nm in the dry state and 5.5 nm in the wet state, respectively, confirming that the polymer electrolyte membrane of this example possessed a microphase-separated structure in both the dry and wet states. The volume swelling ratio was 184%.
[0199] <Example 2> (Synthesis of Polymer (P3)) To a 100 mL three-necked flask equipped with a nitrogen inlet tube, a stirrer, and a Dean-Stark tube, 2.711 g of the hydrophobic monomer (M3) obtained in Synthesis Example 3, 2.664 g of the hydrophilic monomer (M1) obtained in Synthesis Example 1, and 1.352 g of potassium carbonate were added, and nitrogen substitution was performed. Then, 25 mL of DMSO and 25 mL of cyclohexane were added. After heating to 130°C and reflux dehydration for 4 hours, the cyclohexane was removed from the Dean-Stark tube. The reaction mixture was heated to 140°C and polymerization was carried out for 260 hours. After cooling the reaction mixture to room temperature, it was reprecipitated and purified from 500 mL of isopropyl alcohol (IPA), and the solid was recovered by filtration. The recovered solid was washed with water and dried under reduced pressure to obtain a polymer (P3) having a structure represented by the following formula (P3). The yield was 88%. The Mn of the polymer (P3) obtained by measurement in the same manner as in Comparative Example 1 was 33,000, the Mw was 75,000, and the Mw / Mn was 2.3.
[0200] [Chemistry 31]
[0201] [In formula (P3), M represents Na, K or H, and n represents a positive number (about 20).] (Fabrication of Electrolyte Membrane) The polymer electrolyte membrane of Example 2 (an electrolyte membrane containing the proton-substituted polymer (P3)) was obtained by the same method as in Example 1 except that the polymer (P3) was used instead of the polymer (P2). The thickness of the polymer electrolyte membrane was 37 m m.
[0202] (evaluate) The polymer electrolyte membrane of this example was evaluated using the same methods as in Comparative Example 1 (proton conductivity evaluation, hydrogen permeability test, SAXS measurement, and volume swelling ratio measurement). The proton conductivity was 185 mS / cm (80°C, 100% relative humidity), confirming that the polymer electrolyte membrane of this example had good proton conductivity. The hydrogen permeability was 0.14 × 10 -7 cm 3 mm / (cm 2 ·s·kPa) (80°C relative humidity 60%), it was confirmed that the polymer electrolyte membrane of this embodiment has a higher TM NR211 exhibits superior gas barrier properties. SAXS measurements of the interplanar spacing d in the dry and wet states show 3.9 nm and 5.4 nm, respectively, confirming that the polymer electrolyte membrane of this example possesses a microphase-separated structure in both dry and wet states. The volume swelling ratio is 94%.
[0203] <Example 3> (Synthesis of polymer (P4) and preparation of electrolyte membrane) The polymer (P3) obtained in Example 2 was dissolved in DMSO to obtain a solution containing 10% by mass of the polymer (P3). The obtained solution was cast on a glass substrate and dried at 60°C for 12 hours to obtain a film (thickness 37 m m). The obtained membrane was immersed in a mixed solution containing 80 mL of acetic acid, 8 mL of sulfuric acid, and 7 mL of hydrogen peroxide, and stirred at 30°C for 48 hours. Then, it was heated and stirred at 105°C for 10 minutes. The obtained membrane was immersed in pure water to be thoroughly washed, and then dried under reduced pressure to obtain a membrane (film thickness 37) containing a polymer (P4) having a structure represented by the following formula (P4): m m). The Mn of the polymer (P4) obtained by the same method as above was 37,000, Mw was 84,000, and Mw / Mn was 2.3. The infrared absorption spectra of the polymer film before and after the oxidation reaction were measured, and the results were 1570 cm -1 and 1470cm -1 The absorption peak at 1330 cm -1 The absorption peak intensity of 1570cm -1 and 1470cm -1 The absorption peak at 1330 cm-1 is derived from the ring stretching vibration of the benzene ring with -S- bond. -1 The absorption peak of α is derived from the stretching vibration of the -SO2- bond, and thus it was confirmed that the -S- bond was oxidized to the -SO2- bond by the oxidation reaction.
[0204] [Chemistry 32]
[0205] [In formula (P4), M represents Na, K or H, and n represents a positive number (about 20).] The obtained membrane was immersed in 1M hydrochloric acid for 24 hours to remove the metal ions (Na + or K + ) is replaced by a proton (H + ), and then immersed in pure water for thorough washing, and dried under reduced pressure, thereby obtaining the polymer electrolyte membrane of Example 3 (an electrolyte membrane comprising a proton-substituted polymer (P4), with a membrane thickness of 37 m m).
[0206] (evaluate) The polymer electrolyte membrane of this example was evaluated using the same methods as in Comparative Example 1 (proton conductivity evaluation, hydrogen permeability test, SAXS measurement, and volume swelling ratio measurement). The proton conductivity was 172 mS / cm (80°C, 100% relative humidity), confirming that the polymer electrolyte membrane of this example had good proton conductivity. The hydrogen permeability was 0.11×10 -7 cm 3 mm / (cm 2 ·s·kPa) (80°C relative humidity 60%), it was confirmed that the polymer electrolyte membrane of this embodiment has a higher TM NR211 exhibits superior gas barrier properties. SAXS measurements of the interplanar spacing d in the dry and wet states show 3.9 nm and 5.2 nm, respectively, confirming that the polymer electrolyte membrane of this example possesses a microphase-separated structure in both dry and wet states. The volume swelling ratio is 74%.
[0207] <Example 4> (Synthesis of polymer (P5)) To a 100 mL three-necked flask equipped with a nitrogen inlet tube, a stirrer, and a Dean-Stark tube, 0.816 g of the hydrophobic monomer (M4) obtained in Synthesis Example 4, 1.195 g of the hydrophilic monomer (M1) obtained in Synthesis Example 1, and 0.652 g of potassium carbonate were added, and nitrogen substitution was performed. Then, 10 mL of DMSO and 10 mL of cyclohexane were added. After heating to 130°C and reflux dehydration for 4 hours, the cyclohexane was removed from the Dean-Stark tube. The reaction mixture was heated to 140°C and polymerized for 100 hours. After cooling the reaction mixture to room temperature, it was reprecipitated and purified from 300 mL of isopropyl alcohol (IPA), and the solid was recovered by filtration. The recovered solid was washed with water and dried under reduced pressure to obtain a polymer (P5) having a structure represented by the following formula (P5). The yield was 85%. The Mn of the polymer (P5) obtained by measurement in the same manner as in Comparative Example 1 was 28,000, the Mw was 66,000, and the Mw / Mn was 2.4.
[0208] [Chemistry 33]
[0209] [In formula (P5), M represents Na, K or H, and n represents a positive number (about 20).] (Fabrication of Electrolyte Membrane) The polymer electrolyte membrane of Example 4 (an electrolyte membrane containing the proton-substituted polymer (P5)) was obtained by the same method as in Example 1 except that the polymer (P5) was used instead of the polymer (P2). The thickness of the polymer electrolyte membrane was 31 m m.
[0210] (evaluate) The polymer electrolyte membrane of this example was evaluated using the same methods as in Comparative Example 1 (proton conductivity evaluation, hydrogen permeability test, SAXS measurement, and volume swelling ratio measurement). The proton conductivity was 232 mS / cm (80°C, 100% relative humidity), confirming that the polymer electrolyte membrane of this example has good proton conductivity. The hydrogen permeability was 0.13×10 -7 cm 3 mm / (cm 2 ·s·kPa) (80°C relative humidity 60%), it was confirmed that the polymer electrolyte membrane of this embodiment has a higher TM NR211 exhibits superior gas barrier properties. SAXS measurements of the interplanar spacing d in the dry and wet states show 3.4 nm and 5.2 nm, respectively, confirming that the polymer electrolyte membrane of this example possesses a microphase-separated structure in both dry and wet states. The volume swelling ratio is 506%.
[0211] <Example 5> (Synthesis of Polymer (P6)) To a 100 mL three-necked flask equipped with a nitrogen inlet tube, a stirrer, and a Dean-Stark tube, 0.924 g of the hydrophobic monomer (M5) obtained in Synthesis Example 5, 1.087 g of the hydrophilic monomer (M1) obtained in Synthesis Example 1, and 0.593 g of potassium carbonate were added, and nitrogen substitution was performed. Then, 10 mL of DMSO and 10 mL of cyclohexane were added. After heating to 130°C and reflux dehydration for 4 hours, the cyclohexane was removed from the Dean-Stark tube. The reaction mixture was heated to 150°C and polymerized for 120 hours. After cooling the reaction mixture to room temperature, it was reprecipitated and purified from 300 mL of isopropyl alcohol (IPA), and the solid was recovered by filtration. The recovered solid was washed with water and dried under reduced pressure to obtain a polymer (P6) having a structure represented by the following formula (P6). The yield was 94%. The Mn of the polymer (P6) obtained by measurement in the same manner as in Comparative Example 1 was 29,000, the Mw was 59,000, and the Mw / Mn was 2.0.
[0212] [Chemistry 34]
[0213] [In formula (P6), M represents Na, K or H, and n represents a positive number (about 20).] (Fabrication of Electrolyte Membrane) A polymer electrolyte membrane of Example 5 (an electrolyte membrane comprising a proton-substituted polymer (P6)) was obtained by the same method as in Example 1 except that polymer (P6) was used instead of polymer (P2). The thickness of the electrolyte membrane was 52 m m.
[0214] (evaluate) The polymer electrolyte membrane of this example was evaluated using the same methods as in Comparative Example 1 (proton conductivity evaluation, hydrogen permeability test, SAXS measurement, and volume swelling ratio measurement). The proton conductivity was 188 mS / cm (80°C, 100% relative humidity), confirming that the polymer electrolyte membrane of this example had good proton conductivity. The hydrogen permeability was 0.11×10 -7 cm 3 mm / (cm 2 ·s·kPa) (80°C relative humidity 60%), it was confirmed that the polymer electrolyte membrane of this embodiment has a higher TM NR211 exhibits superior gas barrier properties. SAXS measurements of the interplanar spacing d in the dry and wet states show 3.8 nm and 5.6 nm, respectively, confirming that the polymer electrolyte membrane of this example possesses a microphase-separated structure in both dry and wet states. The volume swelling ratio is 114%.
[0215] <Example 6> (Synthesis of Polymer (P7)) To a 100 mL three-necked flask equipped with a nitrogen inlet tube, a stirrer, and a Dean-Stark tube, 0.932 g of the hydrophobic monomer (M6) obtained in Synthesis Example 6, 1.297 g of the hydrophilic monomer (M1) obtained in Synthesis Example 1, and 0.593 g of potassium carbonate were added, and nitrogen substitution was performed. Then, 10 mL of DMSO and 10 mL of cyclohexane were added. After heating to 130°C and reflux dehydration for 4 hours, the cyclohexane was removed from the Dean-Stark tube. The reaction mixture was heated to 150°C and polymerization was carried out for 105 hours. After the reaction solution was allowed to cool to room temperature, it was reprecipitated and purified from 300 mL of isopropyl alcohol (IPA), and the solid was recovered by filtration. The recovered solid was washed with water and dried under reduced pressure to obtain a polymer (P7) having a structure represented by the following formula (P7). The yield was 90%. The Mn of the polymer (P7) obtained by measurement in the same manner as in Comparative Example 1 was 51,000, the Mw was 110,000, and the Mw / Mn was 2.2.
[0216] [Chemistry 35]
[0217] [In formula (P7), M represents Na, K or H, and n represents a positive number (approximately 30).] (Fabrication of Electrolyte Membrane) A polymer electrolyte membrane of Example 6 (an electrolyte membrane comprising a proton-substituted polymer (P7)) was obtained by the same method as in Example 1 except that the polymer (P7) was used instead of the polymer (P2). The thickness of the electrolyte membrane was 27 m m.
[0218] (evaluate) The polymer electrolyte membrane of this example was evaluated using the same methods as in Comparative Example 1 (proton conductivity evaluation, hydrogen permeability test, SAXS measurement, and volume swelling ratio measurement). The proton conductivity was 199 mS / cm (80°C, 100% relative humidity), confirming that the polymer electrolyte membrane of this example had good proton conductivity. The hydrogen permeability was 0.12×10 -7 cm 3 mm / (cm 2 ·s·kPa) (80°C relative humidity 60%), it was confirmed that the polymer electrolyte membrane of this embodiment has a higher TM NR211 exhibits superior gas barrier properties. SAXS measurements of the interplanar spacing d in the dry and wet states show 3.7 nm and 5.5 nm, respectively, confirming that the polymer electrolyte membrane of this example possesses a microphase-separated structure in both dry and wet states. The volume swelling ratio is 47%, confirming that the polymer electrolyte membrane of this example exhibits excellent swelling resistance.
[0219] Comparative Example 3 (Synthesis of Polymer (P8)) To a 100 mL three-necked flask equipped with a nitrogen inlet, a stirrer, and a Dean-Stark tube, 0.498 g of 4,4'-bis[(4-chlorophenyl)sulfonyl]-1,1'-biphenyl, 0.532 g of [1,1'-biphenyl]-4,4'-diol, 1.026 g of the hydrophilic monomer (M1) obtained in Synthesis Example 1, and 1.185 g of potassium carbonate were added, and nitrogen substitution was performed. Then, 10 mL of DMSO and 10 mL of cyclohexane were added. After heating to 130°C and reflux dehydration for 4 hours, the cyclohexane was removed from the Dean-Stark tube. Polymerization was continued while heating to 130°C for 72 hours. After cooling the reaction solution to room temperature, it was purified by reprecipitation from 300 mL of isopropyl alcohol (IPA), and the solid was recovered by filtration. The recovered solid was washed with water and dried under reduced pressure to obtain a polymer (P8) having the structure represented by the following formula (P8). The yield was 94%. The Mn of the polymer (P8) obtained by measurement in the same manner as in Comparative Example 1 was 26,000, the Mw was 69,000, and the Mw / Mn was 2.7.
[0220] [Chemistry 36]
[0221] [In formula (P8), M represents Na, K, or H, l is approximately 0.39 (0.35 to 0.43), m is approximately 0.61 (0.57 to 0.65), and n is approximately 40 (15 to 100).] (Fabrication of Electrolyte Membrane) A polymer electrolyte membrane of Comparative Example 3 (an electrolyte membrane containing a proton-substituted polymer (P8)) was obtained by the same method as in Example 1 except that polymer (P8) was used instead of polymer (P2). The thickness of the polymer electrolyte membrane was 48 m m.
[0222] (evaluate) The polymer electrolyte membrane of this comparative example was evaluated in various ways (proton conductivity evaluation, hydrogen permeability test, SAXS measurement, and volume swelling ratio measurement) using the same methods as in Comparative Example 1. The proton conductivity was 113 mS / cm (80°C, 100% relative humidity), the hydrogen permeability was 0.18 × 10 -7 cm 3 mm / (cm 2 ·s·kPa) (80°C, relative humidity, 60%). No clear scattering peaks were observed in SAXS measurements for either the dry or wet state. The volume swelling ratio was 167%.
[0223] <Example 7> (Synthesis of Polymer (P9)) To a 100mL three-necked flask equipped with a nitrogen inlet tube, a stirrer, and a Dean-Stark tube, 0.985g of the hydrophobic monomer (M2) obtained in Synthesis Example 2, 1.157g of the hydrophilic monomer (M1) obtained in Synthesis Example 1, and 0.668g of potassium carbonate were added, and nitrogen substitution was performed. Then, 10mL of dimethyl sulfoxide (DMSO) and 10mL of cyclohexane were added. After heating to 130°C and reflux dehydration for 4 hours, the cyclohexane was removed from the Dean-Stark tube. Polymerization was carried out while heating to 130°C for 72 hours. Then, 0.004g of decafluorobiphenyl was added, and polymerization was carried out while heating to 130°C for 3.5 hours. After the reaction solution was allowed to cool to room temperature, it was reprecipitated and purified from 300mL of isopropyl alcohol (IPA), and the solid was recovered by suction filtration. The recovered solid was washed with water and dried under reduced pressure to yield a polymer (P9) comprising multiple polymer units having the structure represented by formula (P2) and having three or more decafluorobiphenyl-derived crosslinking groups bonded to these polymer units. The yield was 81.9%. The Mn of the resulting polymer (P9), measured in the same manner as in Comparative Example 1, was 54,000, the Mw was 150,000, and the Mw / Mn ratio was 2.8.
[0224] (Fluorine content determination) The fluorine content of polymer (P9) was measured using the following method. First, combustion gas generated by burning a sample (polymer (P9)) was blown into an aqueous hydrogen peroxide solution, causing the aqueous solution to absorb the fluorine component, thereby obtaining an absorbing solution. Subsequently, the same procedure was repeated without adding a sample to obtain a blank absorbing solution. The fluorine content of the resulting absorbing solution, the blank absorbing solution, and the original absorbing solution was quantified by ion chromatography (IC). The fluorine content of polymer (P9) was 0.1% by mass or less.
[0225] (Fabrication of Electrolyte Membrane) A polymer electrolyte membrane of Example 7 (an electrolyte membrane comprising a proton-substituted polymer (P9)) was obtained by the same method as in Example 1 except that polymer (P9) was used instead of polymer (P2). The thickness of the electrolyte membrane was 62 m m.
[0226] (evaluate) The polymer electrolyte membrane of this example was evaluated using the same methods as in Comparative Example 1 (proton conductivity evaluation, hydrogen permeability test, SAXS measurement, and volume swelling ratio measurement). The proton conductivity was 200 mS / cm (80°C, 100% relative humidity), confirming that the polymer electrolyte membrane of this example had good proton conductivity. The hydrogen permeability was 0.13×10 -7 cm 3 mm / (cm 2 ·s·kPa) (80°C relative humidity 60%), it was confirmed that the polymer electrolyte membrane of this embodiment has a higher TM NR211 exhibits superior gas barrier properties. The interplanar spacing d measured by SAXS in the dry and wet states was 4.0 nm and 5.0 nm, respectively, confirming that the polymer electrolyte membrane of this example possesses a microphase-separated structure in both dry and wet states. The volume swelling ratio was 60%, confirming that the polymer electrolyte membrane of this example possesses excellent swelling resistance.
[0227] <Example 8> (Synthesis of Polymer (P10)) To a 100mL three-necked flask equipped with a nitrogen inlet tube, a stirrer, and a Dean-Stark tube, 2.955g of the hydrophobic monomer (M2) obtained in Synthesis Example 2, 3.526g of the hydrophilic monomer (M1) obtained in Synthesis Example 1, and 2.051g of potassium carbonate were added, and nitrogen substitution was performed. Then, 30mL of dimethyl sulfoxide (DMSO) and 30mL of cyclohexane were added. After heating to 130°C and reflux dehydration for 4 hours, the cyclohexane was removed from the Dean-Stark tube. Polymerization was carried out while heating to 130°C for 72 hours. After cooling to room temperature, 0.014g of decafluorobiphenyl was added, and polymerization was carried out by heating to 130°C for 3.5 hours. After the reaction solution was left to cool to room temperature, it was reprecipitated and purified from 1000mL of isopropyl alcohol (IPA), and the solid was recovered by suction filtration. The recovered solid was washed with water and dried under reduced pressure to obtain a polymer (P10) comprising a plurality of polymer units having a structure represented by formula (P2) and having three or more crosslinking groups derived from decafluorobiphenyl bonded to the polymer units. The yield was 79.3%. The Mn of the polymer (P10) obtained by the same method as in Comparative Example 1 was 71,000, the Mw was 200,000, and the Mw / Mn was 2.8. The fluorine content of the polymer P (10) obtained by the same method as in Example 7 was less than 0.1% by mass.
[0228] (Fabrication of Electrolyte Membrane) A polymer electrolyte membrane of Example 8 (an electrolyte membrane comprising a proton-substituted polymer (P10)) was obtained by the same method as in Example 1 except that polymer (P10) was used instead of polymer (P2). The thickness of the electrolyte membrane was 56 m m.
[0229] (evaluate) The polymer electrolyte membrane of this example was evaluated using the same methods as in Comparative Example 1 (proton conductivity evaluation, hydrogen permeability test, SAXS measurement, and volume swelling ratio measurement). The proton conductivity was 221 mS / cm (80°C, 100% relative humidity), confirming that the polymer electrolyte membrane of this example has good proton conductivity. The hydrogen permeability was 0.12×10 -7 cm 3 mm / (cm 2 ·s·kPa) (80°C relative humidity 60%), it was confirmed that the polymer electrolyte membrane of this embodiment has a higher TM NR211 exhibits superior gas barrier properties. The interplanar spacing d measured by SAXS in the dry and wet states was 4.0 nm and 4.9 nm, respectively, confirming that the polymer electrolyte membrane of this example possesses a microphase-separated structure in both dry and wet states. The volume swelling ratio was 58%, confirming that the polymer electrolyte membrane of this example exhibits excellent swelling resistance.
[0230] <Example 9> (Synthesis of Polymer (P11)) To a 100mL three-necked flask equipped with a nitrogen inlet tube, a stirrer, and a Dean-Stark tube, 0.982g of the hydrophobic monomer (M2) obtained in Synthesis Example 2, 1.139g of the hydrophilic monomer (M1) obtained in Synthesis Example 1, and 1.442g of potassium carbonate were added, and nitrogen substitution was performed. Then, 10mL of dimethyl sulfoxide (DMSO) and 10mL of cyclohexane were added. After heating to 130°C and reflux dehydration for 4 hours, the cyclohexane was removed from the Dean-Stark tube. Polymerization was carried out while heating to 130°C for 72 hours. After cooling to room temperature, 0.004g of decafluorobiphenyl was added, and polymerization was carried out by heating to 130°C for 3.5 hours. After the reaction solution was left to cool to room temperature, it was reprecipitated and purified from 300mL of isopropyl alcohol (IPA), and the solid was recovered by suction filtration. The recovered solid was washed with water and dried under reduced pressure to obtain a polymer (P11) comprising a plurality of polymer units having a structure represented by formula (P2) and having three or more crosslinking groups derived from decafluorobiphenyl bonded to the polymer units. The yield was 78.3%. The Mn of the polymer (P11) obtained by the same method as in Comparative Example 1 was 48,000, the Mw was 230,000, and the Mw / Mn was 4.8. The fluorine content of the polymer P (11) obtained by the same method as in Example 7 was less than 0.1% by mass.
[0231] (Fabrication of Electrolyte Membrane) A polymer electrolyte membrane of Example 9 (an electrolyte membrane comprising a proton-substituted polymer (P11)) was obtained by the same method as in Example 1 except that polymer (P11) was used instead of polymer (P2). The thickness of the electrolyte membrane was 25 m m.
[0232] (evaluate) The polymer electrolyte membrane of this example was evaluated using the same methods as in Comparative Example 1 (proton conductivity evaluation, hydrogen permeability test, SAXS measurement, and volume swelling ratio measurement). The proton conductivity was 203 mS / cm (80°C, 100% relative humidity), confirming that the polymer electrolyte membrane of this example has good proton conductivity. The hydrogen permeability was 0.16×10 -7 cm 3 mm / (cm 2 ·s·kPa) (80°C relative humidity 60%), it was confirmed that the polymer electrolyte membrane of this embodiment has a higher TMNR211 exhibits superior gas barrier properties. The interplanar spacing d measured by SAXS in the dry and wet states was 4.0 nm and 4.9 nm, respectively, confirming that the polymer electrolyte membrane of this example possesses a microphase-separated structure in both dry and wet states. The volume swelling ratio was 55%, confirming that the polymer electrolyte membrane of this example exhibits excellent swelling resistance.
[0233] <Comparative Example 4> (Synthesis of Polymer (P12)) To a 100 mL three-necked flask equipped with a nitrogen inlet, a stirrer, and a Dean-Stark tube, 1.004 g of the hydrophobic monomer (M2) obtained in Synthesis Example 2, 1.182 g of the hydrophilic monomer (M1) obtained in Synthesis Example 1, 0.004 g of decafluorobiphenyl, and 0.673 g of potassium carbonate were added, and nitrogen substitution was performed. Then, 10 mL of dimethyl sulfoxide (DMSO) and 10 mL of cyclohexane were added. After heating to 130°C and reflux dehydration for 4 hours, the cyclohexane was removed from the Dean-Stark tube. Polymerization was continued at 130°C for 72 hours. After cooling the reaction solution to room temperature, it was reprecipitated and purified from 300 mL of isopropyl alcohol (IPA), and the solid was recovered by filtration. The recovered solid was washed with water and dried under reduced pressure to obtain a polymer (P12) with a cross-linked structure. The yield was 59.2%. The polymer (P12) obtained by measurement in the same manner as in Comparative Example 1 had an Mn of 47,000, an Mw of 200,000, and an Mw / Mn of 4.3. It should be noted that in this synthesis example, since decafluorobiphenyl, a crosslinking agent, reacted simultaneously with the hydrophilic monomer (M1) and the hydrophobic monomer (M2), the polymer (P12) had a structure in which structural units derived from the hydrophilic monomer (M1), structural units derived from the hydrophobic monomer (M2), and crosslinking groups derived from decafluorobiphenyl were randomly arranged.
[0234] (Fabrication of Electrolyte Membrane) A polymer electrolyte membrane of Comparative Example 4 (an electrolyte membrane containing proton-substituted polymer (P12)) was obtained by the same method as in Example 1 except that polymer (P12) was used instead of polymer (P2). The thickness of the polymer electrolyte membrane was 63 m m.
[0235] (evaluate) The polymer electrolyte membrane of this comparative example was evaluated in various ways (proton conductivity evaluation, hydrogen permeability test, SAXS measurement, and volume swelling ratio measurement) using the same methods as in Comparative Example 1. The proton conductivity was 179 mS / cm (80°C, relative humidity 100%), the hydrogen permeability was 0.11×10 -7 cm 3 mm / (cm 2·s·kPa) (80°C, relative humidity, 60%). No clear scattering peaks were observed in SAXS measurements in either the dry or wet state. The volume swelling ratio was 81%.
[0236] Comparison between Example 7 and Comparative Example 4 confirmed that cross-linking at the polymer terminal improved the swelling suppression effect and proton conductivity due to cross-linking, compared with a polymer in which cross-linking intervals were random.
[0237] [Table 1]
[0238] This application is based on Japanese Patent Application No. 2023-55171 filed on March 30, 2023, and Japanese Patent Application No. 2024-11288 filed on January 29, 2024, the entireties of which are incorporated herein by reference. All references cited herein are hereby incorporated in their entirety.
Claims
1. A polymer, characterized in that It has the structure shown in the following formula (1): , In formula (1), A 1 represents a structural unit represented by the following formula (a1), A 2 represents a structural unit represented by the following formula (a2), L 1 and L 2 Each independently represents a single bond, -O-, -S- or -SO2-, n represents an integer from 10 to 100, Indicates a bond, Multiple A 1 Same as each other, Multiple A 2 Same as each other, Multiple L 1 Same or different from each other, Multiple L 2 the same as or different from one another; , In formula (a1), IExG represents an ion exchange group, L 3 represents a single bond, -O-, -S-, -SO2- or -CO-, x represents an integer from 2 to 10, Indicates a bond, Multiple IExGs are the same or different from each other. Multiple L 3 the same as or different from one another; , In formula (a2), Ar represents an arylene group having no ion exchange group, L 4 represents a single bond, -O-, -S-, -SO2- or -CO-, y represents an integer from 3 to 20, Indicates a bond, A plurality of Ar's are the same as or different from each other, Multiple L 4 the same as or different from each other.
2. The polymer according to claim 1, wherein The L 1 、the L 2 、the L 3 and the L 4 Each is independently a single bond or -SO2-.
3. The polymer according to claim 1 or 2, wherein The structural unit represented by the formula (a1) includes at least one selected from the group consisting of a sulfo group, an alkylsulfo group, and a sulfonimide group as the ion exchange group.
4. The polymer according to any one of claims 1 to 3, wherein The structural unit represented by the formula (a2) includes at least one selected from a phenylene group, a naphthylene group, and a fluorenyl group as the arylene group.
5. The polymer according to any one of claims 1 to 4, wherein The number average molecular weight of the polymer is 20,000 to 300,000.
6. The polymer according to any one of claims 1 to 5, wherein The polymer is a polymer of a compound represented by the following formula (b1) and a compound represented by the following formula (b2) or an oxide thereof: , In formula (b1), A 1 Same as above, X 1b and X 2b each independently represents a halogen atom; , In formula (b2), A 2 Same as above, Z 1b and Z 2b Each independently represents a hydroxyl group, a thiol group, a halogen atom, a boronic acid group, an alkylborane group or a borate ester group.
7. The polymer according to any one of claims 1 to 6, wherein The polymer comprises a plurality of polymer units having the structure represented by the above formula (1), and There are three or more cross-linking groups bonded to the polymer unit.
8. The polymer according to claim 7, wherein The cross-linking group has one or more aromatic rings, The polymer unit is bonded to the aromatic ring.
9. The polymer according to claim 7 or 8, wherein The polymer is a reaction product of a compound represented by the following formula (b1), a polymer of a compound represented by the following formula (b2), or an oxide thereof, and a compound having three or more groups that react with the polymer or the oxide thereof to form a crosslink: , In formula (b1), A 1 Same as above, X 1b and X 2b each independently represents a halogen atom; , In formula (b2), A 2 Same as above, Z 1b and Z 2b Each independently represents a hydroxyl group, a thiol group, a halogen atom, a boronic acid group, an alkylborane group or a borate ester group.
10. The polymer according to any one of claims 1 to 9, wherein The ratio of the weight average molecular weight to the number average molecular weight is 2.0 to 20.
0.
11. An electrolyte material, characterized in that Contains the polymer according to any one of claims 1 to 10.
12. An electrolyte membrane, characterized in that Contains the polymer according to any one of claims 1 to 10.
13. An electrolyte membrane with a catalyst layer, characterized in that: A method comprising: providing the electrolyte membrane according to claim 12; and a catalyst layer disposed on one or both surfaces of the electrolyte membrane.
14. A membrane electrode assembly, characterized in that: A device comprising the electrolyte membrane according to claim 12 and electrode layers arranged on one or both surfaces of the electrolyte membrane.
15. A solid polymer fuel cell, characterized in that: A membrane electrode assembly according to claim 14 is provided.
16. A solid polymer water electrolysis device, characterized in that: A membrane electrode assembly according to claim 14 is provided.
Citation Information
Patent Citations
Solid polyelectrolyte fuel cell and manufacture thereof
JP1999204119A
Ground improvement device
JP2023055171A
Inverter device and power source device
JP2024011288A
Polymer electrolyte membrane, membrane electrode assembly using same, and solid polymer fuel cell
WO2013031675A1